The Thrity-Seventh Asilomar Conference on Signals, Systems &Amp; Computers, 2003
DOI: 10.1109/acssc.2003.1292339
|View full text |Cite
|
Sign up to set email alerts
|

Design of canonical signed digit IIR fiilters using genetic algorithm

Abstract: Abstracf4n tbis paper, genetic algorithm (GA) is used to design I-D infinite impulse response (IIR) filters witb canonical signed-digit (CSD) coefficients. The filter is realized by cascading second order sections, and tbe stability is guaranteed by constraining the denominator polynomial coellicients of each second order section to be within tbe stability triangle. A new CSD number restoration technique is proposed to restore invalid coefiidents resulted from crossover and mutation operation to CSD coellicieo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…This indicates that the system is prone to feedback and instability. The Digital filters have various stages in their design [14,15] as shown in Figure 1.…”
Section: Iir Filter Design Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the system is prone to feedback and instability. The Digital filters have various stages in their design [14,15] as shown in Figure 1.…”
Section: Iir Filter Design Issuesmentioning
confidence: 99%
“…Moreover, it is computationally very expensive. Ahmadi et al (2003) used genetic algorithm to design 1-D IIR filter with canonical-signed-digit coefficients restricted to low-pass filter. Ahmad and Antoniou (2006) explored FIR filters and equalizers through the use of GA. Consequently GAs requires a large amount of computation.…”
Section: Introductionmentioning
confidence: 99%
“…The most common method [9], [11] is to simply reject any filter that is not stable or give a fitness value of zero, which is virtually the same thing. This method has the same problems associated with it as the CSD constraints of the previous section.…”
Section: Recursive Filtersmentioning
confidence: 99%
“…The genetic algorithm (GA) has obtained large interest in application to digital IIR filter design . In Liang et al, they used GA to design a 1‐D IIR filter with canonical‐signed‐digit coefficients constrained to a low‐pass filter; Ahmad and Antoniou investigated the use of GAs for the design of numerous kinds of digital filters. It was found that GAs require a large amount of computation.…”
Section: Introductionmentioning
confidence: 99%